Europe between financial repression and regulatory - Pagliari, Stefano; Vallée, Shahin; Monnet, Eric (Brussels, 2014)
"The financial crisis modified drastically and rapidly the European financial system’s political economy, with the emergence of two competing narratives. First, government agencies are frequently described as being at the mercy of the financial sector, routinely hijacking political, regulatory and supervisory processes, a trend often referred to as “capture”. But alternatively, governments are portrayed as subverting markets and abusing the financial system to their benefit, mainly to secure better financing conditions and allocate credit to the economy on preferential terms, referred to as “financial repression”. We take a critical look at this debate in the European context. First, we argue that the relationship between governments and financial systems in Europe cannot be reduced to polar notions of “capture” and “repression”, but that channels of pressure and influence bet-ween governments and their financial systems have frequently run both ways and fed from each other. Second, we put these issues into an historical perspective and show that the current reconfiguration of Europe’s national financial systems is influenced by history but is not a return to past interventionist policies. We conclude by analysing the impact of the reform of the European financial architecture and the design of a European banking union on the configuration of national financial ecosystems."